2019
DOI: 10.1177/1179546819849428
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Viscosity and NLR in Young Subjects with Myocardial Infarction: Evaluation at the Initial Stage and at 3 and 12 Months

Abstract: In the “Sicilian study on juvenile myocardial infarction,” we had evaluated plasma viscosity (PV) and neutrophil/lymphocyte ratio (NLR) in patients with acute myocardial infarction (AMI) at the age of ⩽45 years. Now, we examined the relationship between these 2 parameters in 120 subjects (109 men and 11 women) aged ⩽45 years with recent AMI. The patients were classified according to the number of cardiovascular risk factors, the electrocardiographic criteria (ST-segment elevation myocardial infarction [STEMI] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In patients diagnosed with NSTEMI, an elevated NLR was found to be correlated with a higher incidence of atrial fibrillation and heart failure, a reduced left ventricular ejection fraction and increased rates of coronary artery bypass grafting (CABG). Others have shown that NLR following hospitalization is a significant and autonomous indicator of both one-year reinfarction and mortality rates among individuals with AMI who also have diabetes [ 5 , 6 , 7 , 8 , 9 ]. NLR was shown to be a prognostic factor for hospitalization and long-term prognosis in patients with STEMI receiving PCI in two meta-analyses that included more than 10,000 patients each [ 10 , 11 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In patients diagnosed with NSTEMI, an elevated NLR was found to be correlated with a higher incidence of atrial fibrillation and heart failure, a reduced left ventricular ejection fraction and increased rates of coronary artery bypass grafting (CABG). Others have shown that NLR following hospitalization is a significant and autonomous indicator of both one-year reinfarction and mortality rates among individuals with AMI who also have diabetes [ 5 , 6 , 7 , 8 , 9 ]. NLR was shown to be a prognostic factor for hospitalization and long-term prognosis in patients with STEMI receiving PCI in two meta-analyses that included more than 10,000 patients each [ 10 , 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, when assessed alongside other factors such as hemorheological determinants, plasma markers of platelet and neutrophil activation, oxidative stress, elastase and protein oxidation, it was found to be a valuable indicator [ 2 ]. In the same line, two parameters, NLR and plasma viscosity (PV), which were examined concurrently in a prospective study which included young AMI subjects at 3 and 12 months following AMI, exhibited distinct patterns, indicating a substantial decrease in NLR during the follow-up period, while PV did not exhibit a similar change, being the only variable that demonstrated discriminant ability in relation to the cardiovascular complications observed over an 18-month follow-up [ 6 ]. NLR is subject to the influence of both diet and physical exercise.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we have not disregarded neither the behavior of erythrocyte deformability nor the red cell distribution width (RDW), although in part of the entire cohort of these patients, we have previously observed a reduction in erythrocyte deformability, explored with whole blood filtration and diffractometric technique, with respect to the group of healthy volunteers. 11 The erythrocyte deformability is dependent on the surface/ volume ratio of the erythrocyte, on internal viscosity related mainly to the concentration of cytosolic calcium, on erythrocyte organic phosphates (ATP and 2.3 DPG), and changes in hemoglobin, and it is also dependent on the dynamic membrane properties, related to the protein and lipid composition. In addition to allowing the erythrocyte to easily cross microvascular districts of a few microns, so much lower than the geometric characteristics of the red blood cell (RBC), the deformability plays a specific role in the supply to oxygen to tissues.…”
Section: Introductionmentioning
confidence: 99%